2020
DOI: 10.1002/mnfr.202000437
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and its Effects on DNA Methylation in Development, Aging, and Disease

Abstract: DNA methylation is increasingly being recognized as a mechanism through which environmental exposures confer disease risk. Several studies have examined the association between vitamin D and changes in DNA methylation in areas as diverse as human and animal development, genomic stability, chronic disease risk, and malignancy. In many cases, they have demonstrated clear associations between vitamin D and DNA methylation in candidate disease pathways. Despite this, a clear understanding of the mechanisms by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Several epigenetic effects of VD have been described in a number of models and pathophysiological contexts. These effects include DNA methylation, possibly through modulation of DNA methyltransferase and/or DNA demethylase expression [ 52 ]. VD can also regulate histone acetylation via activation of histone acetyltransferases and histone deacetylases, but also histone methylation and demethylation, thus modulating chromatin accessibility to transcription factors [ 53 ].…”
Section: Metabolism Of the Vitamin Dmentioning
confidence: 99%
“…Several epigenetic effects of VD have been described in a number of models and pathophysiological contexts. These effects include DNA methylation, possibly through modulation of DNA methyltransferase and/or DNA demethylase expression [ 52 ]. VD can also regulate histone acetylation via activation of histone acetyltransferases and histone deacetylases, but also histone methylation and demethylation, thus modulating chromatin accessibility to transcription factors [ 53 ].…”
Section: Metabolism Of the Vitamin Dmentioning
confidence: 99%
“…Despite the exact relationship between diet and the epigenome remains unclear, several studies reported an association between epigenetic modifications and dietary depletion or supplementation (1,(42)(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…The genomic effect of vitamin D through VDR receptors is thought to be effective in the pathogenesis of health and diseases such as cancer, metabolic syndrome, obesity, diabetes, skin diseases, immunity, inflammation, and organ transplantation-related complications [4]. In addition to these genomic effects of Vit D, it is also known to have epigenetic effects by activating signaling pathways, DNA methylation and histone acetylation [5].…”
Section: Introductionmentioning
confidence: 99%